Analysis of Vicious Circle of Poverty, the Social Role of Micro Waqf Bank, and Permissiveness of Street Vendors in Rural Indonesia - Dahlan, Rahmat; Trihastuti, Aselina Endang; Pangestu, Raden Ali; Sitasari, Ita; Syaiin, Emmy Hamidiyah; Fauzi, Muhamad (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2025)
Purpose: This study examines the social function of micro waqf banks and the permissive attitude of street vendors in breaking the cycle of poverty in rural areas.Design/Methodology: The study employs a qualitative method with a descriptive approach, using a purposive sample of 100 consumers from Bita Amanah Ummat Micro Waqf Bank in Garut Regency, West Java. Data were collected through interviews with two consumer group leaders, observations, and literature reviews. The collected data were then analysed using source triangulation.Findings: The findings reveal eight dimensions of the vicious cycle of poverty, identified through interview and field observations. The social role of micro-waqf institutions helps street vendors develop a more optimistic outlook on poverty. The data indicate that education (64%) is the most frequently mentioned concern, followed by social participation (76%), culture (59%), employment (52%), marital relationships (48%), health (35%), justice (21%), and housing (19%). The primary challenge faced by micro waqf bank customers in breaking the poverty cycle includes inadequate capital, low productivity, insufficient income, weak demand, and lack of investment.Practical implications: The study highlights the necessity of multi-faceted approach to poverty alleviation, with education as a key intervention. Addressing poverty effectively requires an integrated strategy that combines education, employment, social support, and policy reform to foster sustainable change.Originality/Value : The study integrates aspects of education, health, justice, employment, culture, housing, partnerships, and social participation as fundamental elements in breaking the vicious cycle of poverty among micro waqf bank customers.